Practice on prevention of gastritis among undergraduates of Faculty of Allied Health Sciences, University of Jaffna - Jayasooriya, R.L.A.S.; Atapattu, A.M.P.R.; Jegapragash, V.; Vathulan, S. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2023)
Introduction: Gastritis is a common inflammatory disease condition. The most common cause is Helicobactor phylori infection. It adversely affects the quality of life as well as end-up with life threatening conditions such as gastric cancer. Therefore, having good practices on prevention of gastritis is important. Objective: To assess the practice on prevention of gastritis among undergraduates of Faculty of Allied Health Sciences, University of Jaffna. Methodology: This descriptive cross-sectional study was done among 426 undergraduates of Faculty of Allied Health Sciences, University of Jaffna selected by stratified random sampling method. Data were collected by using the pretested self-administered questionnaire. Descriptive statistics was used to describe the data and the associated factors were found by using chi squared test. The ethical clearance was obtained from the Ethics Review Committee of Faculty of Medicine, University of Jaffna. Results: The response rate was 91.07%. Among them two third of the participants were female (67.5%). Mean age of the participants was 23.8years (SD=0.625). In the findings 43% of the participants had been diagnosed with gastritis., 46.1% were having good practice on prevention with the mean of 47.6 (SD= 7.678). Majority of the participants were following bad practices on prevention like eating uncooked food (70.9%), skipping more than one meal in a day (63.1%), eating high spicy foods (67%), eating fast foods (66.8%), high salty intake (71.4%), and high citrus intake (72.4%). Further, this study revealed that a smaller number of participants were following the good practices like washing hands before meal (50.8%), following clean technique on food handling (47.9%), getting meal on proper time (45.9%), referring about practice on prevention (46.1%), following stress realising techniques (53.1%), and doing regular physical exercises (41.7%). Conclusion: This study found that less than half of the participants only had good practice on practice on prevention of gastritis. The study concludes that the practice of prevention of gastritis were poor among undergraduates.
Keywords: Gastritis; Practice on prevention; Undergraduates